RHUS CORIARIA LINN, A PLANT OF MEDICINAL, NUTRITIONAL AND INDUSTRIAL IMPORTANCE: A REVIEW - Arham Shabbir (Journal of Animal and Plant Sciences, 2012)
Rhus coriaria Linn. (Anacardiacea), commonly known as sumac, has been used as a spice, condiment, appetizer, and as a souring agent for centuries. A broad range of nutritionally and medicinally significant phytochemical components have been identified from various parts of sumac such as tannins, flavonoids, anthocyanins, organic acids, flavones, proteins, fiber, volatile oils, nitrates, and nitrites. The plant also possesses minerals which are beneficial in the treatment of different disorders and contribute to various biological processes. In traditional system of medicine, this plant has been used in the treatment of diarrhea, dysentery, ulcer, hemorrhoids, hemorrhage, wound healing, hematemesis, hemoptysis, leucorrhea, sore throat, ophthalmia, conjunctivitis, diuresis, animal bites, poison, pain, and liver disease. Traditional practitioners have also prescribed this plant as antimicrobial, abortifacient, and stomach tonic. Rhus coriaria is known to possess DNA protective, non-mutagenic, chondroprotective, antifungal, antibacterial, antioxidant, anti-ischemic, vasorelaxant, hypoglycemic, xanthine oxidase inhibition, vascular smooth muscle cell migration inhibition, and hepatoprotective properties, supporting its traditional uses. The role of plant in leather and textile industry as tanning agent and as a coloring agent is significant. It also prevents wood decay and has considerable potential for future research.
Keywords: Rhus coriaria; phytochemistry; antioxidant; antibacterial; sumac